ADAR1 expression is associated with tumour-infiltrating lymphocytes in triple-negative breast cancer - In Hye Song; Young-Ae Kim; Sun-Hee Heo; In Ah Park; Miseon Lee; Won Seon Bang; Hye Seon Park; Gyungyub Gong; Hee Jin Lee (Tumor Biology)
Tumours with a high mutation burden exhibit considerable neoantigens and tumour-infiltrating lymphocytes. RNA editing by ADAR1 is a source of changes in epitope. However, ADAR1 expression in cancer cells and tumour-infiltrating lymphocyte levels in triple-negative breast cancer have not been well evaluated. We immunohistochemically examined ADAR1 expression in 681 triple-negative breast cancer patients and analysed their clinicopathological characteristics. We also analysed basal-like tumours using The Cancer Genome Atlas data. Among the 681 triple-negative breast cancer patients, 45.8% demonstrated high ADAR1 expression. Tumours with high ADAR1 expression exhibited high tumour-infiltrating lymphocyte levels, considerable CD8 + T lymphocyte infiltration, high histological grade and high expression of interferon-related proteins, including HLA-ABC, MxA and PKR. Among patients with lymph node metastasis, those with high tumour-infiltrating lymphocyte levels and low ADAR1 expression demonstrated the best disease-free survival. The Cancer Genome Atlas data analysis of basal-like tumours revealed significant positive correlation between ADAR1 and CD8B expression and positive association of high ADAR1 expression with immune responses and apoptosis pathways. We detected high ADAR1 expression in half of the triple-negative breast cancer patients. In addition to DNA mutations, RNA editing can be related to neoantigens; hence, we need to explore non-synonymous mutations exclusively found using RNA sequencing data to identify clinically relevant neoantigens.